The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1253/circj.cj-12-0264
|View full text |Cite
|
Sign up to set email alerts
|

Normal Range of Left Ventricular 2-Dimensional Strain

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp wo-dimensional (2-D) speckle tracking echocardiography (STE) is being increasingly used for the quantification of global and regional left ventricular (LV) mechanics. 1,2 Previous studies have validated the accuracy of STE against cardiac magnetic resonance imaging, a reference standard. 3, 4 The superiority of STE compared with LV ejection fraction has been reported in several clinical settings. 5-7 The rapid adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(84 citation statements)
references
References 22 publications
6
73
1
4
Order By: Relevance
“…Among 193 subjects who were enrolled to determine intervendor variability in the Japanese Ultrasound Speckle Tracking of the Left Ventricle study, 10 we selected 81 subjects aged $20 years (GE vs Philips in 26 subjects, Philips vs Toshiba in 31 subjects, and GE vs Toshiba in 24 subjects). The subjects were enrolled from four hospitals in Japan and were primarily hospital employees, their relatives, and other volunteers recruited via advertising.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 193 subjects who were enrolled to determine intervendor variability in the Japanese Ultrasound Speckle Tracking of the Left Ventricle study, 10 we selected 81 subjects aged $20 years (GE vs Philips in 26 subjects, Philips vs Toshiba in 31 subjects, and GE vs Toshiba in 24 subjects). The subjects were enrolled from four hospitals in Japan and were primarily hospital employees, their relatives, and other volunteers recruited via advertising.…”
Section: Subjectsmentioning
confidence: 99%
“…Recent studies have demonstrated that intervendor peak strain values measured by vendor-specific software in the same subjects are frequently different and incomparable. [7][8][9][10] In clinical situations, the majority of ultrasound laboratories use several ultrasound machines from different vendors for routine echocardiographic examinations. Therefore, any longitudinal studies evaluating changes in strain values using 2D speckle-tracking software should consider the reliability of results obtained using different vendor-specific software algorithms.…”
mentioning
confidence: 99%
“…These results, are not influenced by the base-apex positioning and by the type of machine used [3] . Diagrams of the figure 5 summarize those contradictory MR and STE published results.…”
Section: Figure 5 Comparison Of Published Regional Ecc Values Obtainmentioning
confidence: 55%
“…If we consider regional Ecc analysis, largely investigated through single modality studies (STE or MR-tagging performed separately), highest lateral absolute Ecc is constantly reported in MR-based literature [5,[16][17][18][19][20][21] and highest septal absolute Ecc is constantly reported in the STE based literature [3,4,10,11,22,23] . These results, are not influenced by the base-apex positioning and by the type of machine used [3] .…”
Section: Figure 5 Comparison Of Published Regional Ecc Values Obtainmentioning
confidence: 99%
See 1 more Smart Citation